Turning Research Ideas into Reality: A Guide to Developing a Simulated Research Protocol using Administrative Data - Prior, Heather J.; Sirski, Monica; Taylor, Carole (International Journal of Population Data Science, 2024)
Objectives Demonstrate the translation of a research idea into a protocol with an analytic plan, including discussion on requirements for administrative data (AD) analysis, e.g., governance, time estimation. Foster discussion on processes for conducting AD research to enable learning and collaboration. Approach Participants were guided through three sections, and each alternated between presentations, group participation and discussion sessions. An overview of the Manitoba Centre for Health Policy (MCHP) Data Repository was presented to use as the framework for the AD discussion. Our chosen topic of discussion was: “How do health history and family history affect risk of poor outcomes for people with diabetes?” In small groups, participants discussed issues arising from translating the idea into a research plan. For example, define a cohort of people with diabetes, examine cardiovascular events as the outcome using survival analysis, and control for demographics, treatment compliance and family history of diabetes and cardiovascular events. We evaluated the feasibility of using AD to measure these variables. We discussed a method to estimate the time to conduct this proposed using AD, i.e., time for programming and analysis. Finally, we discussed data approvals and requirements when conducting research using AD. Conclusions and Implications We discussed the benefits and cautions of using AD and shared knowledge regarding research opportunities and obstacles across jurisdictions to identify commonalities and areas of opportunity for growth. The workshop was informative and interactive. It generated much discussion and was well-received among participants, with many asking for further information after the workshop concluded.